A new multiple input multiple output multi-carrier direct sequence code division multiple access system using T × T spreading with link budget analysis. (2016) - Sheikh, Javaid A.; Parah, Shabir A.; Bhat, G. Mohiuddin
High data rates and High Quality of Service (QOS) are the main requirements in Next Generation Networks (NGNs). The communication channel needs to be shared in an efficient manner. An interesting technique is based on spread spectrum and orthogonal coding sequence called Code Division Multiple Access (CDMA). Owing to performance and implementation complexity issues, multi-user detection methods are mainly restricted in high data transmission rate CDMA. In this paper, a low complex multi-user Multi-Carrier CDMA (MC-CDMA) receiver is proposed and implemented, which employs time (T) domain spreading at both coding and modulation ends and consequently increases the processing gain. The performance comparison of the proposed technique and the conventional schemes has been performed in terms of bit error rate. The results of the link budget analysis have been provided in terms of reports generated by link budget software of Bonsai Networks.